Two-Layered Susceptibility Vessel Sign on 3-Tesla T2*-Weighted Imaging Is a Predictive Biomarker of Stroke Subtype. Issue 1 (January 2015) - Yamamoto, Nobuaki; Satomi, Junichiro; Tada, Yoshiteru; Harada, Masafumi; Izumi, Yuishin; Nagahiro, Shinji; Kaji, Ryuji
<x xml:space="preserve">Abstract</x> Background and Purpose— A susceptibility vessel sign (SVS) on 1.5-tesla (T)-T2*-weighted images may predict cardioembolism. It has also been detected in patients with large artery atherosclerosis. In patients with major vessel occlusion, the SVS was comprised 2 layers on 3T-T2*-weighted images. We assessed the efficacy of 2-layered SVS on 3T-T2*-weighted imaging scans for predicting cardioembolism. Methods— Our study included 132 patients who had ischemic stroke within the preceding 24 hours and presented with internal carotid artery or middle cerebral artery occlusion because of cardioembolism or large artery atherosclerosis. We compared 2-layered SVS and SVS on 3T-T2*-weighted imaging scans for their sensitivity, specificity, and diagnostic odds ratio for predicting cardioembolism. Results— We enrolled 132 patients (72 men; mean age, 74.5 years); of these, 63 (47.7%) were presented with cardioembolism. Although the sensitivity of SVS and 2-layered SVS for cardioembolism and large artery atherosclerosis was not statistically different (74.6% and 58.0%, respectively), the sensitivity of 2-layered SVS was significantly higher in patients with cardioembolism (42.9%) than those with large artery atherosclerosis (2.9%; P<0.001). The specificity and diagnostic odds ratio for 2-layered SVS for cardioembolism were 97.1% and 25.1; for SVS they were 42.0% and 2.1, respectively. Conclusion— The specificity of 2-layered SVS for cardioembolism was high. It may be useful for predicting cardioembolism and for the management of patients with acute ischemic stroke.